Arbuscular Mycorrhizal Fungi and Nutrition Determine the Outcome of Competition Between Lolium multiflorum and Trifolium subterraneum - Unger, Stephan; Habermann, Franziska M.; Schenke, Katarina; Jongen, Marjan (Frontiers in Plant Science, 2021)
Arbuscular mycorrhizal fungi (AMF) may affect competitive plant interactions, which are considered a prevalent force in shaping plant communities. Aiming at understanding the role of AMF in competition between two pasture species and its dependence on soil nutritional status, a pot experiment with mycorrhizal and non-mycorrhizal Lolium multiflorum and Trifolium subterraneum was conducted, with manipulation of species composition (5 levels), and nitrogen (N) and phosphorus (P) fertilization (3 levels). In the non-mycorrhizal state, interspecific competition did not play a major role. In the presence of AMF, however, Lolium was the stronger competitor, with this species being facilitated by Trifolium. While N-fertilization did not change the competitive balance, P-fertilization gave Lolium a competitive advantage over Trifolium. The effect of AMF on the competitive outcome may be driven by differential C-P trade benefits, with Lolium modulating carbon investment in the mycorrhizal network and the arbuscule / vesicle ratio at the cost of Trifolium.